HAVE 34 PROVINCES IN INDONESIA SUCCESSFULLY IMPLEMENTED FINANCIAL AUTONOMY? EVIDENCE FROM APBD 2004-2020 - Muhammad Hamdan Sayadi (Jurnal Akuntansi dan Pajak, 2022)
The regional government financial statement can be used to measure the financial performance of an area whether it is classified as good or bad. Through the financial statement, a region can know whether it has implemented regional autonomy in financial terms or not. This study aims to analyze and describe the level of regional financial dependence on 34 provinces in Indonesia for the period 2004 - 2020. This research is classified as a quantitative descriptive method and uses regional financial dependency ratio as an analysis tool. The results showed that the provincial financial autonomy located on the island of Java was much better than the provinces outside the island of Java. There were 5 provinces that had a moderate level of dependence on the central government, 4 provinces with a sufficient dependency level, and 5 provinces with high dependency level. Meanwhile, the other 20 provinces had a very high level of dependence on the central government. The financial autonomy of provincial governments in Indonesia for the period 2004 - 2020 had not been implemented properly because there were 20 provinces with a high level of dependence on the central government or around 58.82%.